The Effectiveness of the Students’ Vocabulary Handbook of ‎English Course at Zahanain Islamic Boarding School - Hadi Prayitno Hadi; Abd. Aziz Wahab; Zainuddin (Hasanuddin University, 2023)
This study investigated teaching strategies to develop students' vocabulary in conducting the research. This research uses the descriptive qualitative method. This study analyzed the data obtained through observation, interview, and questionnaire methods descriptively. A literature review was carried out. The findings show that interactive media in handbooks influences learning in teaching vocabulary in the Zahanain English Course. The literature study also found that interactive media greatly influenced students' motivation and involvement in learning vocabulary. Teachers are encouraged to use interactive teaching media in developing students' vocabulary. Cultural, educational background, and traditional teaching practices in Zahanain English Course are identified to be the factors that contribute to many students' heavy reliance on memorization as their sole approach to vocabulary learning. In addition to rote memorization, which has been proven useful and effective in the Zahanain English course ELT context, this paper suggests that students be presented with vocabulary learning strategies and be taught how to build vocabulary through other useful learning methods.